"Электронный нос" на основе матрицы элементарных полупроводниковых резистивных сенсоров - Altukhov, A. A.; Mityagin, A. Yu.; Shustrov, A. V. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
A novel chemical sensor, referred to as an "electronic nose," has been developed on the basis of a matrix-type polysensor structure. The device includes 16 individual gas sensors, a computer control program, and a mathematical software package for data processing.